HUBUNGAN POWER OTOT LENGAN BAHU DAN KOORDINASI MATA TANGAN DENGAN HASIL KETEPATAN SERVIS ATLET TENIS LAPANGAN PPLP RIAU - Yandi, Ardi; Ramadi, Ramadi; Vai, Aref (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: The aim of this study is to determine whether there is a connection between shoulder arm muscle strength and hand-eye coordination with the accuracy of the services of Riau PPLP athletes. The samples from this study were PPLP Riau tennis athletes, for 12 people. The sampling technique was taken in total (total sampling) or the complete sampling technique in tennis athletes in PPLP Riau, which was 12 people. The results of the correlation in PPLP Riau field tennis athletes where the first analysis between shoulder arm force X1 and Y where rtab at a significant level ? (0.05) = r count (0.457) <r_tab (0.735) means that the hypothesis is accepted and that there is a moderate relationship between strength shoulder arm muscles serving the ability tennis tennis athletes PPLP Riau. From the analysis of the analysis of both X2 and Y, where r_tab is at a significant level ? (0.05) = r_count (0.410) <r_tab (0.735), meaning that the hypothesis is accepted and that there is a link between hand coordination of the service capacity of tennis athletes in Riau PPL Third analysis of arm muscle strength relationship (X1) hand eye coordination (X2) with lower passing results (Y) where rtab at siignificant level ? (0.05) = r_count (0.507) <r_tab (0.735) can be cooncluded that the relationship between (X1) and (X2) with (Y) or the relationship between shoulder arm muscle and hand-eye coordination with the accuracy of PPLP Riau athlete service is on interventionKey Words: Shoulder Muscle Strength, Coordination and Service.